The gene expression profiles of induced pluripotent stem cells (iPSCs) generated by a non-integrating method are more similar to embryonic stem cells than those of iPSCs generated by an integrating method - Liu,Yajun (2012)
Induced pluripotent stem cells (iPSCs) obtained by the ectopic expression of defined transcription factors have tremendous promise and therapeutic potential for regenerative medicine. Many studies have highlighted important differences between iPSCs and embryonic stem cells (ESCs). In this work, we used meta-analysis to compare the global transcriptional profiles of human iPSCs from various cellular origins and induced by different methods. The induction strategy affected the quality of iPSCs in terms of transcriptional signatures. The iPSCs generated by non-integrating methods were closer to ESCs in terms of transcriptional distance than iPSCs generated by integrating methods. Several pathways that could be potentially useful for studying the molecular mechanisms underlying transcription factor-mediated reprogramming leading to pluripotency were also identified. These pathways were mostly associated with the maintenance of ESC pluripotency and cancer regulation. Numerous genes that are up-regulated during the induction of reprogramming also have an important role in the success of human preimplantation embryonic development. Our results indicate that hiPSCs maintain their pluripotency through mechanisms similar to those of hESCs.